EFFECTIVENESS OF SOFOSBUVIR AND RIBAVIRIN IN HEPATITIS C GENOTYPE 3 RELAPSERS - Jawaid, Ayehsa Hafiza; Muhammad, Noor; Khan, Hammad Muhammad; Ali, Owais Muhammad; Shah, Mohsin Ali; Saad, Muhammad; Jawaid, Fatima Hafiza (Journal of Ayub Medical College Abbottabad, 2021)
Background: Combination of DAAs, Sofosbuvir and Ribavirin has been known as an effective treatment for HCV genotype 3. The aim of our study is to assess the efficacy of Sofosbuvir and Ribavirin in relapsed HCV genotype 3 patients. Methods: A cross-sectional retrospective analysis of hospital records between January 2015 and December 2016. Data was taken of only those patients who were followed for one year. A total of 193 cases were included in this study who were HCV genotype 3 relapsers and out of these 28 patients failed to be followed. Data was entered and analysed in IBM SPSS software package 23. Results: Out of the total 193 cases, 74.1% of cases achieved RVR at 4 weeks of therapy. ETR was achieved by 91.2% cases, while 8.8% of cases were non-responders. There was statistical significance in gender achieving ETR with a p-value of .008. 84.5% of cases achieved SVR-12. Statistical significance was noted between haemoglobin levels at presentation and 4 weeks follow-up with a p-value <0.005, and also between 4 weeks and 12 weeks follow-up with a p-value <0.005. Statistical significance was also found between age and PCR at 4 weeks (p-value of .002), age and PCR at 24 weeks (p-value of .051) and between ALT levels and PCR at 4, 12 and 24 weeks follow up (p-value <0.005). At 1-year follow-up, 79.3% of cases achieved a negative PCR, 28 patients failed to be followed, 6.2% of cases had a positive PCR. 5.5% of cases of the total 163 SVR cases had a relapse at 1 year. Conclusion: HCV genotype 3 patients can benefit from Sofosbuvir and Ribavirin. With the SVR of more than 80%, this combination is cost-effective and safe. Treatment duration should be dependent on RVR and viral load at 4 weeks follow-up. Keywords: HCV; Sofosbuvir; Ribavirin; Genotype; RVR; SVR